The Future of Coral Reefs Subject to Rapid Climate Change: Lessons from Natural Extreme Environments - Camp, Emma F.; Schoepf, Verena; Mumby, Peter J.; Hardtke, Leonardo A.; Rodolfo-Metalpa, Riccardo; Smith, David J.; Suggett, David J. (Frontiers in Marine Science, 2018)
Global climate change and localised anthropogenic stressors are driving rapid declines in coral reef health. In vitro experiments have been fundamental in providing insight into how reef organisms will potentially respond to future climates. However, such experiments are inevitably limited in their ability to reproduce the complex interactions that govern reef systems. Studies examining coral communities that already persist under naturally-occurring extreme and marginal physicochemical conditions have therefore become increasingly popular to advance ecosystem scale predictions of future reef form and function, although no single site provides a perfect analogue to future reefs. Here we review the current state of knowledge that exists on the distribution of corals in marginal and extreme environments, and geographic sites at the latitudinal extremes of reef growth, as well as a variety of shallow reef systems and reef-neighbouring environments (including upwelling and CO2 vent sites). We also conduct a synthesis of the abiotic data that have been collected at these systems, to provide the first collective assessment on the range of extreme conditions under which corals currently persist. We use the review and data synthesis to increase our understanding of the biological and ecological mechanisms that facilitate survival and success under sub-optimal physicochemical conditions. This comprehensive assessment can begin to: (i) highlight the extent of extreme abiotic scenarios under which corals can persist, (ii) explore whether there are commonalities in coral taxa able to persist in such extremes, (iii) provide evidence for key mechanisms required to support survival and/or persistence under sub-optimal environmental conditions, and iv) evaluate the potential of current sub-optimal coral environments to act as potential refugia under changing environmental conditions. Such a collective approach is critical to better understand the future survival of corals in our changing environment. We finally outline priority areas for future research on extreme and marginal coral environments, and discuss the additional management options they may provide for corals through refuge or by providing genetic stocks of stress tolerant corals to support proactive management strategies.